Prioritisasi Strategi dan Aksi Dekarbonisasi Hulu Migas Melalui Adaptasi Instrumen CLIMACT Prio untuk Mendukung Target Net Zero Emission - Ida Dwi Maharani; Arie Dipareza Syafe’i (Dampak, 2026)
The upstream oil and gas industry faces stringent regulatory pressures through Law No. 7 of 2021 on Carbon Tax and PROPER assessments under MoEF Regulation No. 7 of 2025, which demand innovation in energy efficiency and GHG emission reduction. This study aims to prioritize decarbonization strategies at PT Pertamina EP Sukowati Field by adapting the CLIMACT Prio instrument. The novelty of this research lies in modifying the instrument from a city-scale to an industrial-scale by integrating the Carbon Tax Avoidance Index (CTAI) variable and PROPER innovation criteria. The research method utilizes a Multi-Criteria Decision Analysis (MCDA) approach involving 7 experts through a participatory process. The results show a total baseline GHG emission of 87,564.81 tons CO2e/year, dominated by Gas Turbine units (61.98%). Based on expert weighting, the Capital Expenditure (CAPEX) (21.7%) and Technology Readiness Level (TRL) (20.7%) criteria are the primary considerations. The final ranking results place Fuel Optimization on Prime Movers as the top priority strategy (score 0.75) due to its high emission reduction effectiveness (1,085.49 tons CO2e/year) and the most favorable CTAI value. The subsequent priority strategies are Rooftop Solar PV (0.72), VSD Installation (0.67), and LED Retrofit (0.42). This adapted instrument provides a significant contribution for upstream oil and gas practitioners in formulating measurable and applicable decarbonization roadmaps in PT Pertamina EP Sukowati Field.